A CROSS-SECTIONAL STUDY ON THE FREQUENCY OF VITAL SIGNS MEASUREMENT AND MISSED OPPORTUNITIES AMONG IN-PATIENTS IN MEDICAL AND SURGICAL WARDS AT MBARARA REGIONAL REFERRAL HOSPITAL IN UGANDA. - Nabiddo, Viola; Nambozi, Grace (Student's Journal of Health Research Africa, 2025)
Background Monitoring and recording vital signs is part of routine clinical care and a fundamental nursing procedure in hospitals. Repeated measurement provides early warning scores that assist in noticing a patient who is at risk of deterioration and hence prevent morbidity and mortality in hospitals. This study assessed the frequency of vital signs measurement and missed measurements among in-patients on medical and surgical wards at MRRH. Method A quantitative retrospective study using files of patients who were admitted and discharged between May 2020 and October 2020 in the medical and surgical wards of MRRH was conducted. 243 patient files were used in this study. Information on vital signs (Temp, PR, RR, BP, and SpO2) in patient files was collected. Results 131(53.9%) were files of male, 76(31.3%) had gastrointestinal conditions as their diagnosis on the ward, and 2573(66.2%) of the patients’ vital signs were not recorded from admission to discharge on both medical and surgical wards. Most patients 7(47%) died at night than during day or evening time. The majority of patients with prolonged hospital stays 13, 81.3%) and deaths 2, 50%) had respiratory conditions on a medical ward. In the surgical ward, the majority of patients with prolonged hospital stays 14, 87.5%) were patients with musculoskeletal conditions, and more deaths 5, 45.5%) occurred in patients with gastrointestinal conditions. Missed opportunities were seen in all conditions, and they were all more than >50%. Conclusion Most of the patient files reviewed had missed vital signs from admission to discharge on both medical and surgical wards. Missed opportunities were seen in patients with life-threatening conditions. Recommendation Nurse staffing levels should be paid attention to, and vital sign equipment should be availed to these wards to ensure that vital signs are monitored and the quality of care to patients is improved.